2001
DOI: 10.1124/mol.59.3.636
|View full text |Cite
|
Sign up to set email alerts
|

Glucuronidation of the Nonsteroidal Antiestrogen EM-652 (SCH 57068), by Human and Monkey Steroid Conjugating UDP-Glucuronosyltransferase Enzymes

Abstract: EM-652 (SCH 57068) is a new orally active antiestrogen that demonstrates pure antagonistic effects in the mammary gland and endometrium. In vivo studies have shown that EM-652 is primarily glucuronidated at the 7-hydroxy position in rats and that the metabolite is present in the plasma of female monkeys and human subjects after EM-800 (SCH 57050) or EM-652.HCl oral administration. Using hepatic microsomes from rat, monkey, and human, the formation of two EM-652 monoglucuronides at positions 4' and 7 was demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…To ascertain the expression of the wild-type and mutant UGT1A10 proteins, 10 g of microsomal protein from HEK293 cells stably expressing human wild-type UGT1A10 or mutant UGT1A10 were separated by 10% SDS-polyacrylamide gel electrophoresis. The gel was transferred onto a nitrocellulose membrane and probed with the antihuman UGT1 common carboxyl terminus region antiserum RC-71 (1:2000 dilution) (Barbier et al, 2001). To show the relative amount of proteins loaded in each lane of the Western blot, the same blot was subsequently probed with an anticalnexin CT antibody (StressGen Biotechnologies, Victoria, British Columbia, Canada; 1:1000 dilution).…”
Section: Methodsmentioning
confidence: 99%
“…To ascertain the expression of the wild-type and mutant UGT1A10 proteins, 10 g of microsomal protein from HEK293 cells stably expressing human wild-type UGT1A10 or mutant UGT1A10 were separated by 10% SDS-polyacrylamide gel electrophoresis. The gel was transferred onto a nitrocellulose membrane and probed with the antihuman UGT1 common carboxyl terminus region antiserum RC-71 (1:2000 dilution) (Barbier et al, 2001). To show the relative amount of proteins loaded in each lane of the Western blot, the same blot was subsequently probed with an anticalnexin CT antibody (StressGen Biotechnologies, Victoria, British Columbia, Canada; 1:1000 dilution).…”
Section: Methodsmentioning
confidence: 99%
“…22 For Western blot experiments, UGT1A3-HK293 microsomes (2 g) or total proteins from hepatocytes (5 g) were immunoblotted with an anti-UGT1A (1:2,000) antibody as previously described. 21 Glucuronidation Assays and Determination of Bile Acid Glucuronides in Culture Media and Plasma. In vitro glucuronidation assays were performed for 1 hour in the presence of CDCA or LCA (100 mol/L) and 10 g microsomes in a glucuronidation assay buffer as described.…”
Section: Methodsmentioning
confidence: 99%
“…UGT1A3-HK293 cells were obtained and cultured as described. 21 For RNA and protein analyses, 350,000 hepatocytes/well were seeded in 24-well plates and cultured in the Invitro Gro CP medium for 48 hours. Cells were then treated with vehicle [dimethylsulfoxide (DMSO), 0.1% v/v] or T0901317 (0.1 and 1 mol/L) for 24 hours in the Invitro Gro Hi medium.…”
Section: Methodsmentioning
confidence: 99%
“…In aerobic environment, aerobic bacteria were several folds more active than anaerobic ones [70]. A recent study has isolated bacteria that transformed fE1 into fE2, resulting in further increase in manures' estrogenic activity since a transformation of fE1 to fE2 results in two folds increase in estrogenic activity [71]. In addition, estrogen glucuronates and sulfates both exhibited comparable de-conjugation of conjugated estrogens in manure in oxidative and reductive environment, although D'Ascenzo et al [72] and Hutchins et al [73] have shown that sulfate-conjugated estrogen are more recalcitrant to biodegradation.…”
Section: Effects Of Aerobic and Anaerobic Digestions On Estrogen Concmentioning
confidence: 99%